Origami influence on container design - Kleanthis Antoniou; Erkan Oterkus (Annals of Limnology and Oceanography - Peertechz Publications, 2019)
This study examines the capabilities that the origami tradition can contribute to the structural efficiency of a container. Art and tradition meet engineering in an effort to modify the mechanical properties of a conventional design and broaden its potential, as a heavy and sensitive motor is to be transported in a secure way. Using Finite Element Analysis, a thorough research is being conducted, so that an optimal arrangement of different elements can be found. Mechanical hinges, folding that enables expansion and shrinkage, and a layout that inverts the Poisson's ratio of a structure, are some features that are derived by designs that are primarily Origami conceptions. All these are being put to the test, in an investigation of their effect on stress minimization on the proposed model.